Insertion/Deletion Polymorphism of Angiotensin Converting Enzyme Gene in Kawasaki Disease - Shim, Yoon Hee (The Korean Academy of Medical Sciences, 2006)
Polymorphism of angiotensin converting enzyme (ACE) gene is reported to be associated with ischemic heart disease, hypertrophic cardiomyopathy, and idiopathic dilated cardiomyopathy. In this study, we investigated the relationship between Kawasaki disease and insertion/deletion polymorphism of ACE gene. Fifty five Kawasaki disease patients and 43 healthy children were enrolled. ACE genotype was evaluated from each of the subjects' DNA fragments through polymerase chain reaction (PCR). Frequencies of ACE genotypes (DD, ID, II) were 12.7%, 60.0%, 27.3% in Kawasaki group, and 41.9%, 30.2%, 27.9% in control group respectively, indicating low rate of DD and high rate of ID genotype among Kawasaki patients (p<0.01). Comparing allelic (I, D) frequencies, I allele was more prevalent in Kawasaki group than in control group (57.3% vs. 43.0%, p<0.05). In Kawasaki group, both genotype and allelic frequencies were not statistically different between those with coronary dilatations and those without. ACE gene I/D polymorphism is thought to be associated with Kawasaki disease but not with the development of coronary dilatations.